Analysing Current Research Trends In Islamic Economics And Finance - Nurul Adilah Hasbullah; Muhammad Iqmal Hisham Kamaruddin; Amalina Mursidi; Norfhadzilahwati Rahim; Suhaida Herni Suffarruddin (USIM Press, 2026)
This paper aims to present the results of various bibliometric patterns of articles published in the International Islamic Economics System Conference (I-iECONS) 2023 e-proceedings. This study manually analysed 98 articles from the I-iECONS 2023 e-proceedings. The analysis covers several dimensions, comprising of general information (including types of articles, authorship patterns, authors contributions, geographical affiliation and genders, article lengths and languages, and number of references), keywords used, type of case countries, and research themes. Based on the findings, extended abstracts became the most published articles in this e-proceedings. Meanwhile, authorship patterns highlight majority are co-authored works. Majority of authors are female, Malaysian background, and Universiti Sains Islam Malaysia (USIM) dominate the geographical affiliation. Furthermore, most articles are written in English and have a length between 5-20 pages. In terms of keywords, the most used word is “Malaysia” and “waqf”. Moreover, Islamic social finance such as zakat, waqf and takaful became the most focused theme in the I-iECONS 2023 e-proceedings. This paper incorporates multiple analytical approaches, bibliometric, thematic, and demographic analysis as a comprehensive overview especially on Islamic economics and finance research study.